2014
DOI: 10.1021/jp5038969
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Structure of Metal Mediated (Cytosine)2Ag+ Mimics the Hemiprotonated (Cytosine)2H+ Dimer in i-Motif Folding

Abstract: The study of metal ion-DNA interaction aiming to understand the stabilization of artificial base pairing and a number of noncanonical motifs is of current interest, due to their potential exploitation in developing new technological devices and expanding the genetic code. A successful strategy has been the synthesis of metal-mediated base pairs, in which a coordinative bond to a central metal cation replaces a H-bond in a natural pair. In this work, we characterized, for the first time, the gas phase structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 44 publications
2
51
1
Order By: Relevance
“…In presence of ions, the distances between nitrogen atoms of cytosines were increased manually to the distance of NÁ Á ÁAgÁ Á ÁN (0.21 nm) in agreement with the results reported in Ref. [28]. Corresponding exemplary results for [(C:H:C) + ] 3 , [(C:Cu:C) + ] 3 and [(C:Li:C) + ] 3 including backbone and sugar moieties are shown in the Supporting Information.…”
Section: Numerical Detailssupporting
confidence: 91%
See 1 more Smart Citation
“…In presence of ions, the distances between nitrogen atoms of cytosines were increased manually to the distance of NÁ Á ÁAgÁ Á ÁN (0.21 nm) in agreement with the results reported in Ref. [28]. Corresponding exemplary results for [(C:H:C) + ] 3 , [(C:Cu:C) + ] 3 and [(C:Li:C) + ] 3 including backbone and sugar moieties are shown in the Supporting Information.…”
Section: Numerical Detailssupporting
confidence: 91%
“…[20][21][22][23][24][25] Although a few computational studies already investigated ion-mediated nucleobase pairing effects via electronic structure calculations, the underlying stabilization or destabilization mechanisms are not yet fully understood. [18,[26][27][28][29][30] Specifically the influence of water and π − π interactions between stacked nucleobases, which were often ignored in previous works, are known to change the stability of DNA conformations significantly. [31][32][33][34][35] With regard to a more careful analysis of these contributions, [31][32][33][34][35] the question arises which factors determine the stability of ion-mediated cytosine pairs?…”
mentioning
confidence: 99%
“…It is well known that upon formation of a first Ag + -ligand bond defining the z-axis, s-dσ hybridization occurs in order to reduce the electron density along the z-axis. 37 This is a consequence of the additional stabilization of the base pair through a Hbond between both cytosine molecules, which is not feasible when Ag + interacts on one of C(2)=O (7) groups. This phenomenon has been observed for gas phase Ag + complexes.…”
Section: [Cag-h 2 O] + -1 [Cag-h 2 O] + -2 [Cag-h 2 O]mentioning
confidence: 99%
“…Very recently, it has been reported that Ag + can induce the formation of non-canonical DNA pairs such as silver mediated cytosine pair (Cyt 2 Ag + ). 27,28,30 Whereas the excited state lifetime of Cyt is short, 31,32 which is identified as one of the photoprotection mechanisms of DNA, [7][8][9]11,12,33 it was also shown that the lifetime of the Cyt 2 Ag + complex is long, 34 which means that the effect of this cation on the electronic properties of the DNA bases could be very important. We report here the UV photofragmentation spectrum of the gas phase Cytosine-Ag + (CytAg + ) complex as a reductionist approach to gain information about the effect of Ag + on the optical properties of the DNA bases and especially on the mutagenic role of this cation.…”
Section: Introductionmentioning
confidence: 99%